Cardiometabolic Risk Assessments by Body Mass Index z-Score or Waist-to-Height Ratio in a Multiethnic Sample of Sixth-Graders - Henry S. Kahn; Laure El ghormli; Russell Jago; Gary D. Foster; Robert G. McMurray; John B. Buse; Diane D. Stadler; Roberto P. Treviño; Tom Baranowski; HEALTHY Study Group (Hindawi Limited, 2014)
Convention defines pediatric adiposity by the body mass index z-score (BMIz) referenced to normative growth charts. Waist-to-height ratio (WHtR) does not depend on sex-and-age references. In the HEALTHY Study enrollment sample, we compared BMIz with WHtR for ability to identify adverse cardiometabolic risk. Among 5,482 sixth-grade students from 42 middle schools, we estimated explanatory variations (R2) and standardized beta coefficients of BMIz or WHtR for cardiometabolic risk factors: insulin resistance (HOMA-IR), lipids, blood pressures, and glucose. For each risk outcome variable, we prepared adjusted regression models for four subpopulations stratified by sex and high versus lower fatness. For HOMA-IR, R2 attributed to BMIz or WHtR was 19%-28% among high-fatness and 8%-13% among lower-fatness students. R2 for lipid variables was 4%-9% among high-fatness and 2%-7% among lower-fatness students. In the lower-fatness subpopulations, the standardized coefficients for total cholesterol/HDL cholesterol and triglycerides tended to be weaker for BMIz (0.13-0.20) than for WHtR (0.17-0.28). Among high-fatness students, BMIz and WHtR correlated with blood pressures for Hispanics and whites, but not black boys (systolic) or girls (systolic and diastolic). In 11-12 year olds, assessments by WHtR can provide cardiometabolic risk estimates similar to conventional BMIz without requiring reference to a normative growth chart.